Functional Genomics - Meroni, Germana; Petrera, Francesca; Meroni, Germana; Petrera, Francesca (IntechOpen, 2012)
This book titled "Functional Genomics" contains a selection of chapters focused on crucial topics in functional genomics, from the analysis of the genetic code, to the understanding of the role of the different genes and to the proteomic implications. The book provides an overview on basic issues and some of the recent developments in medicinal science and technology. Covering all the aspects involved in such a broad theme as functional genomics and in all its applications would be impossible within the same book. The different chapters represent a brief introduction to the topic, connecting the most promising developments in functional genomics technologies, focusing on specific applications in biomedicine, agro-food technologies and zootechniques.
English
Keywords: Medical genetics; Medical genetics